Análise de imagens: deterioração de sementes de alface e potencial fisiológico - Lima, Kelly Andressa Peres de (2022)
Elevated temperatures during the germination process of lettuce seeds (Lactuca sativa L.) cause alterations in the seedlings depending on the initial vigor presented by those seeds. Through image analysis it is possible to quickly and accurately evaluate the physiological potential of seeds and through the accelerated aging test its resistance to the stress caused by temperature is evaluated. The objective of this research is to use the ImageJ image processing program to evaluate the vigor and resistance to heat stress of lettuce seeds subjected to accelerated aging. The cultivars Grand Rapids, Moana and Palmas were tested by submitting them to accelerated aging at a temperature of 41°C for 0 (control), 24, 48 and 72 hours. Then, the water content of the seeds was determined and the germination, first count, electrical conductivity, emergence in bed, emergence speed index, dry mass and the analysis of images of the seedlings in ImageJ with three and seven days after sowing. A completely randomized design (DIC) was used with 12 treatments and four replications of 50 seeds. The results were tested by means of analysis of variance (ANOVA) and linear regression analysis at 5% of significance in the SISVAR software. Image analysis identified cv. Moana as the most resistant to high temperature followed by cv. Palmas and cv. Grand Rapids, respectively. The measurement of shoot and total lengths of lettuce seedlings in ImageJ at three and seven days was efficient to identify the vigor and resistance to heat stress of lettuce cultivars. Due to the alterations it causes in the length of the seedlings, accelerated aging together with image analysis allows for an assertive and early characterization of differences in vigor between lettuce cultivars.